2020
DOI: 10.3390/molecules25061385
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Neochlorogenic Acid Extract from Mulberry Leaf (Morus alba L.) Against LPS-Stimulated Inflammatory Response through Mediating the AMPK/Nrf2 Signaling Pathway in A549 Cells

Abstract: Neochlorogenic acid (nCGA) is a phenolic compound isolated from mulberry leaf (Morus alba L.), which possesses multiple pharmacological activities containing antioxidant and anti-inflammatory effects. However, the role of nCGA in the treatment of acute pneumonia and the underlying molecular mechanism are still unclear. Hence, the aim of study is to investigate the anti-inflammatory properties of nCGA on LPS-stimulated inflammation in A549 cells. In the present study, results reported that nCGA without cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 44 publications
2
52
0
Order By: Relevance
“…The effects of CGAs on different aspects of human health have been summarized and discussed [ 2 , 3 ]. The antiviral activity of chlorogenic acid against influenza A virus [ 4 ] and the possible application of CGAs as a natural anti-inflammatory agent for the treatment of acute pneumonia [ 5 ] are also worth mentioning.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of CGAs on different aspects of human health have been summarized and discussed [ 2 , 3 ]. The antiviral activity of chlorogenic acid against influenza A virus [ 4 ] and the possible application of CGAs as a natural anti-inflammatory agent for the treatment of acute pneumonia [ 5 ] are also worth mentioning.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 3,5-DiCQA and other chlorogenic acids have been associated to anti-virus-cell fusion properties against numerous human viruses like human immunodeficiency virus, influenza A, herpes simplex 1 and 2, Coxsackie B3, adenovirus and respiratory syncytial viruses [17][18][19] . In parallel to these anti-viral activities, 3,5-DiCQA has also been assigned as a potent antiinflammatory compound against lipopolysaccharide-induced acute lung injury through the inhibition of human neutrophil elastase activity, making it a potential new therapeutic candidate against acute viral pneumonia diseases 20,21 . Finally, 3,5-DiCQA has also been identified as a hypotensive molecule, inhibiting angiotensin Iconverting enzyme (ACE) 22,23 .…”
mentioning
confidence: 99%
“…Flavonoids and phenolic acids, presenting in mulberry leaf, were the large number of phytochemicals [24]. It was also found that the mulberry leaf is rich polyphenols, such as neochlorogenic acid, chlorogenic acid, rutin, quercetin, astragalin, and kaempferol [25], and the mulberry bioactive compounds showed the antioxidative capacity and anti-in ammatory effects [13,26]. The anti-oxidant effect of mulberry leaf avonoids was associated with increased SOD, CAT and GSH-PX expression, as well as reduced MDA levels [27,28].…”
Section: Discussionmentioning
confidence: 99%